BHP abundances and ratio in Effingham Inlet and Deer Bay - Stephanie Kusch; Stuart G Wakeham; Nadia Dildar; Chun Zhu; Julio Sepúlveda (PANGAEA, 2021)
Bacteriohopanepolyol abundances and ratios were studied in suspended particulate matter obtained along the redoxcline in Effingham Inlet (lat 49.07, long -125.15; 120m water depth) and Deer Bay (lat 49.22, long -125.60; 40m water depth), Vancouver Island, to infer chemo(auto)trophy in these fjords. Water column suspended particulate matter samples were obtained from Vancouver Island fjords using McLane WTS-LV (standard configuration) in situ filtration systems aboard R/V Barnes in July 2007.